2001
DOI: 10.1034/j.1600-0455.2001.042001101.x
|View full text |Cite
|
Sign up to set email alerts
|

ESTIMATION OR QUANTIFICATION OF TUMOUR VOLUME?. CT study on irregular phantoms

Abstract: Subjective size estimation of irregular tumours should be repeatedly performed by the same observer, or by using the mean or median estimate of several observers. Computer-based methods are even more reliable and their use is especially recommended for film readers with limited radiological experience. Only every fourth slice may be measured without a major loss of measurement accuracy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2003
2003
2012
2012

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 10 publications
0
1
0
Order By: Relevance
“…In patients with advanced head and neck cancer, Rudat et al [27] reported precision and reliability of the CT based volume measurements by repeated measurements using irregularly shaped phantoms. Furthermore, Titola et al [28] proposed that one-dimensional volume estimation of irregularly shaped tumor-like phantoms should be substituted by true computer-based volume calculations.…”
Section: Discussionmentioning
confidence: 99%
“…In patients with advanced head and neck cancer, Rudat et al [27] reported precision and reliability of the CT based volume measurements by repeated measurements using irregularly shaped phantoms. Furthermore, Titola et al [28] proposed that one-dimensional volume estimation of irregularly shaped tumor-like phantoms should be substituted by true computer-based volume calculations.…”
Section: Discussionmentioning
confidence: 99%